EMPOWERING CHILDREN FOR PARTICIPATORY DISASTER MITIGATION: A DEVELOPMENT COMMUNICATION APPROACH IN KUBU RAYA, WEST KALIMANTAN - Fernando, Joshua; Supiyandi, Andi; Utomo, Budi; Hildawati, Hildawati; Shukla, Aditya Kumar (ASPIRATION Journal, 2025)
Kubu Raya Regency in West Kalimantan is a region with a high level of disaster risk. Based on the 2022 Indonesian Disaster Risk Index (IRBI), Kubu Raya is categorized as high risk due to its geographic conditions, which are dominated by lowlands, swamps, and large rivers. Despite various mitigation programs, children's involvement in these processes remains minimal, even though they have the potential to be agents of change in their communities. This study aims to identify forms of participatory communication for children in disaster mitigation. This approach is based on the view that development communication not only conveys information but also empowers communities through active participation, including children's communities. The research used a qualitative Participatory Action Research (PAR) approach, grounded in the Risk Communication Theory of Covello & Sandman. The study involved children from the Ambawang Kubu Raya Forum Anak community. They were involved in flood risk mapping activities, evacuation simulations, and the production of community-based disaster campaign media. This study concluded that participatory communication is effective in helping children identify flood hazards based on their experiences and observations. Through the Child-Friendly Participatory Geographic Information Systems approach, children not only visually mapped risks but also strengthened their spatial awareness and engagement in building community resilience. Furthermore, they articulated an ideal, healthy, safe, inclusive environment and expressed their desire to participate in mitigation actions actively. These findings demonstrate that a development communication approach that involves children directly strengthen communities' adaptive capacity in disaster-prone areas.